JURASSIC HERITAGE OF PORTUGAL: STATE OF THE ART AND OPEN PROBLEMS (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2004)
The aim of this work is to present a general view on the situation of Jurassic sites outcropping in Portugal, in particular those located in the Lusitanian Basin, which represent geosites with heritage value. The legal instruments on geoconservation are generically presented, and they happen to be designed for Natural Heritage deeply confused with the Biological Heritage. No specific law for geological values exist in Portugal, but the general law on Natural Conservation has allowed the protection of five geosites of national relevance as Natural Monuments. They correspond to a small area when compared to the whole national area of Protected Sites, and they all correspond to dinosaur tracksites of Jurassic and Cretaceous age. Geosites of regional relevance have been also protected using municipal laws and they show important public use, sometimes giving rise to reference museums and to continuous pedagogical actions. On the other hand, geosites of international relevance for its stratigraphic value (the Bajocian GSSP at Cabo Mondego section, the candidate to the Toarcian GSSP at Peniche section) have no formal protection and classification according to the Portuguese laws. They remain safe because they are located on the coast, which is protected due to other environmental laws. Their integration in a supra-national framework supported by UNESCO is obviously recommended and it would be of great impact among the national institutions with formal responsibilities on the Natural Heritage.